Show that f'(a) = g(a) ?

  • Thread starter jkristia
  • Start date
  • #1
54
0

Homework Statement



Problem:
1C-2 Let f(x) = (x - a)g(x). Use the definition of the derivative to calculate that f'(a) = g(a), assuming that g is continuous



Homework Equations





The Attempt at a Solution



I just started a self study of calculus using Khan and MIT OpenCourse. I am bit stuck, or maybe confused, with this exercise from MIT 18.01

The definition for the derivative is
[itex]\frac{Δy}{Δx}[/itex]=[itex]\frac{f(x)-f(a)}{x-a}[/itex]

I can replace f(x) with (x-a)g(x), but I don't know what to do with f(a). In the given solution f(a) somehow becomes 0, but I can't see how.

The given solution:
attachment.php?attachmentid=47038&stc=1&d=1336362033.png


Any help is much appreciated.
 

Attachments

  • 1C-2-solution.png
    1C-2-solution.png
    2.4 KB · Views: 384

Answers and Replies

  • #2
LCKurtz
Science Advisor
Homework Helper
Insights Author
Gold Member
9,559
770
f(a) = (a-a)g(a) = 0.
 
  • #3
54
0
ah - of course. Thank you very much
 

Related Threads on Show that f'(a) = g(a) ?

Replies
9
Views
722
  • Last Post
Replies
2
Views
810
Replies
0
Views
4K
  • Last Post
Replies
9
Views
1K
Replies
5
Views
1K
Replies
9
Views
561
  • Last Post
Replies
3
Views
729
  • Last Post
2
Replies
31
Views
4K
  • Last Post
Replies
3
Views
459
Top